Scientific perspectives on Guillain-Barre Syndrome (GBS): A comprehensive review for sentience after early 2025 GBS outbreak in an Indian state - Patil, Sarika J; Bhosale, Rohit R; Chavan, Dhanashri D; Yadav, Akshay R; Patil, Swapnil S (Creative Pharma Assent, 2025)
Background: Guillain-Barré Syndrome (GBS) is an acute, self-limiting, and rare neurological disorder wherein the body's immune system mistakenly attacks the peripheral nervous system (PNS). A report, published in February 2025 by the Indian newspaper ‘The Times of India’, highlighted a significant outbreak of GBS in the Indian state of Maharashtra, owing to the Campylobacter jejuni (C. jejuni) infection. The surge in cases has been considered as one of the most significant recorded GBS outbreaks globally, which underscores the need to raise GBS awareness. Method: This article provides an in-depth scientific perspective on GBS, drawing on literature from scientific databases such as PubMed and ScienceDirect. It aims to enhance awareness among science-related students, researchers, medical and paramedical professionals, and the general public. Result and discussion: GBS is an acute polyneuropathy characterized by limb weakness with hyporeflexia or areflexia. In severe forms, respiratory and bulbar paralysis can occur, requiring mechanical ventilatory support. It is the commonest cause of acute neuromuscular paralysis. The basic underlying mechanism of the disease is a localized attack against the myelin sheath of the peripheral nerves and nerve roots, with secondary axonal damage. It is believed that the bacterial antigens have a close molecular mimicry with neural antigens. As a result, the response generated against these antigens cross-reacts with the neural cells. Plasma exchange, immunoglobulin infusion, and plasmapheresis are the mainstays of treatment for GBS. Conclusion: A thorough understanding of GBS is essential, including its pathophysiology, underlying causes, risk factors, symptoms, diagnostic methods, treatment strategies, and the latest advancements.